2023
DOI: 10.1101/2023.06.02.543457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-resolution structure of mouse radial spoke and its in-situ structure in ependymal cilia revealed by cryo-EM and cryo-ET

Abstract: Radial spokes (RS) transmit mechanochemical signals between the central pair (CP) and axonemal dynein arms to coordinate ciliary motility. However, the high-resolution structure of mammalian RS remains missing. Here, we present the high-resolution cryo-EM structure of mouse RS head-neck complex in both monomer and dimer forms and reveal the intrinsic dynamics of the dimer. We also map the genetic mutations related to primary ciliary dyskinesia and asthenospermia on the head-neck complex. Moreover, we present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Nevertheless, the image resolutions were still insufficient for a definite conclusion whether the entire axonemal ultrastructure was the same as the wild-type one (Fig. 7b) (Meng et al, 2023). Interestingly, we observed that, while BFs were oriented towards a similar direction in the wild-type ependymal cells, a state termed the rotational polarity of BBs (Ohata and Alvarez-Buylla, 2016), BFs in Kif6 -/ependymal cells were misoriented regardless of the severity of hydrocephalus (Fig.…”
Section: Kif6 Is Crucial For the Rotational Polarity Of Bbs In Ependy...mentioning
confidence: 74%
“…Nevertheless, the image resolutions were still insufficient for a definite conclusion whether the entire axonemal ultrastructure was the same as the wild-type one (Fig. 7b) (Meng et al, 2023). Interestingly, we observed that, while BFs were oriented towards a similar direction in the wild-type ependymal cells, a state termed the rotational polarity of BBs (Ohata and Alvarez-Buylla, 2016), BFs in Kif6 -/ependymal cells were misoriented regardless of the severity of hydrocephalus (Fig.…”
Section: Kif6 Is Crucial For the Rotational Polarity Of Bbs In Ependy...mentioning
confidence: 74%